(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
This research is devoted to investigate experimentally the flexural behavior of cold-formed steel I-beam with strengthened hollow rectangular flange (RHFCFSIB) under four point loads at the same distance from the support. All specimens have the constant clear span of (L=1500mm), a constant beam specifications (t=4mm) web and flange thickness , (h=300mm) for beam′s depth and flange width of (bf=150mm) and flange depth of (hf=60mm) .The spacing between the bolts that connect the web to the flanges was (L/6) and eight stiffener for each beam were placed under the load bearing points and at the support points on each side. The experimental program includes assembling the parts to make beams and testing of five specimens tested under four point loads, one of these specimens was not strengthened, which used as a control specimen. Four specimens strengthened with different strengthening materials, light weight, cost and strength are the main factors for choosing this material (normal concrete, normal concrete has been replaced coarse aggregate by recycled concrete, normal concrete has been replaced fine aggregate with 30% sawdust and normal concrete has been replaced fine aggregate with 30% coarse rubber). The strengthening beams were compared with the control specimens, It was found from this compaction that strengthening the flange with different strengthening materials improved the behavior of the beam, as the bearing capacity increased in rates ranging between 15.8% and 27.98%, the deflection decreased in rates ranging between 65% and 83% , this means that strengthening flange has a strong influence on the flexural behavior. The main conclusions drawn from the study were discussed and summarized, the research shows that the strengthening hollow flanged sections gave best results for flexural behavior.